2010
DOI: 10.1111/j.1468-0467.2010.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Urban networks and governance in city‐region planning: state‐led region building in nanjing city‐region, china

Abstract: During the transition towards a more marketoriented economy and entrepreneurial governance, local authorities have attempted to create new cross-jurisdiction regional entities to enhance their competitiveness through making cityregion plans or regional strategic plans in China. This article analyses the process of region building in China through a case study of Nanjing city-region. We argue that region building is a state-led regional project in China, not a spontaneous process. City-region planning has playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Despite the proliferation of regional development policies in China (Luo et al, 2010;Xu & Yeh, 2011), they are largely not institutionalized (Yeh & Xu, 2008). In a case that might provide insights to that trend this study suggests that the SCJ city-region integration project has not engendered an upscaling of the municipal government or a downscaling of the provincial government towards the city-region scale.…”
Section: Conclusion: On the Disjuncture Between Rhetoric And Realitymentioning
confidence: 75%
See 1 more Smart Citation
“…Despite the proliferation of regional development policies in China (Luo et al, 2010;Xu & Yeh, 2011), they are largely not institutionalized (Yeh & Xu, 2008). In a case that might provide insights to that trend this study suggests that the SCJ city-region integration project has not engendered an upscaling of the municipal government or a downscaling of the provincial government towards the city-region scale.…”
Section: Conclusion: On the Disjuncture Between Rhetoric And Realitymentioning
confidence: 75%
“…In recent years, there has been a renaissance of regional policies and planning across China (Li & Wu, 2012Luo, Shen, & Chen, 2010;Wong, Qian, & Zhou, 2008;Xu & Yeh, 2011). Different from past redistributive and allocative regional policies, recent approaches place emphasis on interjurisdictional co-operation and integration (Xu & Yeh, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…One example is the study by Wang et al (2020a), which proposed the optimization of regional transportation planning based on city network research from the perspective of traffic flow but did not discuss the application path specifically. Luo et al (2010) emphasized the importance of the city network perspective on the importance of the institutional building of regional planning in China from the perspective of theoretical analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the state-orchestrated tie-up in YRD is based on existing functional connectivity and a long history of regional cooperation and building experiments (Chien & Gordon, 2008;Luo & Shen, 2009;Xu, 2008). Previous studies have shown that several trans-provincial regional alliances have taken places, such as Shanghai-Kunshan (Chien, 2013;Luo & Shen, 2009) and Nanjing-Maanshan (Luo, Shen, & Chen, 2010).…”
Section: Introductionmentioning
confidence: 99%